2016
DOI: 10.1007/978-3-319-25474-6_4
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of Working Memory in Speech-in-noise Identification for Listeners with Normal Hearing

Abstract: With the advent of cognitive hearing science, increased attention has been given to individual differences in cognitive functioning and their explanatory power in accounting for inter-listener variability in understanding speech in noise (SiN). The psychological construct that has received most interest is working memory (WM), representing the ability to simultaneously store and process information. Common lore and theoretical models assume that WM-based processes subtend speech processing in adverse perceptua… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
57
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 54 publications
(60 citation statements)
references
References 24 publications
2
57
1
Order By: Relevance
“…Thus, although the sentence identification task we presented requires working memory for storing the sequence of five words, the performance on this task appeared to be more strongly limited by failures of selective attention than by memory aspects. This result is compatible with previous data indicating that working memory capacity and speech identification in noise are associated in older, hearing-impaired participants (see Akeroyd, 2008), while in normal hearing subjects this correlation is weaker or even absent (Füllgrabe and Rosen, 2016). Thus, measures of selective attention should be included in future studies instead of focusing only on working memory capacity.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Thus, although the sentence identification task we presented requires working memory for storing the sequence of five words, the performance on this task appeared to be more strongly limited by failures of selective attention than by memory aspects. This result is compatible with previous data indicating that working memory capacity and speech identification in noise are associated in older, hearing-impaired participants (see Akeroyd, 2008), while in normal hearing subjects this correlation is weaker or even absent (Füllgrabe and Rosen, 2016). Thus, measures of selective attention should be included in future studies instead of focusing only on working memory capacity.…”
Section: Discussionsupporting
confidence: 93%
“…As additional cognitive measures, working memory capacity (e.g., Akeroyd, 2008; Füllgrabe and Rosen, 2016) measured in a sentence span test (Daneman and Carpenter, 1980), and processing speed (e.g., Salthouse, 1996; Tun and Wingfield, 1999) measured by the RT in the neutral condition of the visual flanker task, were included as potential predictors of speech-in-noise identification. The latter was measured in a simulated cocktail-party listening situation with two competing speakers that were presented 25° to the left and right of the target speaker, who was positioned in front of the listener (azimuthal angle 0°).…”
Section: Introductionmentioning
confidence: 99%
“…However, in addition, this group of listeners also shows an engagement of working memory across all tested listening conditions, as long as they at least require the perception of words (Heinrich, Henshaw, & Ferguson, 2016). These results speak to the large body of studies that have investigated the role of working memory for speech perception ever since Akeroyd (2008) suggested that "measures of working memory (especially reading span) were mostly effective [predictors of speech recognition in noise]", and concur with Füllgrabe and Rosen (2016) who suggest that the involvement of working memory for speech perception might be modulated by task difficulty, and might be strongest either due to hearing impairment, adverse environmental factors such as complex fore-and background stimuli, or unfavourable personal factors such as reduced proficiency of perceptual and cognitive abilities. One overarching model that has attempted to formalize these suggestions is the Ease-of-Language-Understanding (ELU) model (Rönnberg et al, 2013) that suggests larger involvement of working memory in speech perception when bottom-up and top-down information are mismatched.…”
Section: Environmental Factorssupporting
confidence: 77%
“…This differential relation between CI and NH listeners is consistent with recent findings. Füllgrabe and Rosen have demonstrated that neurocognitive skills (particularly working memory capacity) contribute little to NH listeners' performance on tasks of speech recognition in noise, in contrast with several studies in adults with hearing loss . Third, it could be that testing listeners under noise conditions that provide greater informational masking (e.g., multi‐talker babble), rather than the energetic masking provided by speech‐shaped noise here, would allow us to better observe top‐down processing contributions to speech recognition.…”
Section: Discussionmentioning
confidence: 90%